PENERAPAN DIGITAL SIGNATURES UNTUK OTENTIKASI DAN KEAMANAN DATA BERBASIS LOKASI GPS PADA APLIKASI MOBILE - Sumarno Sumarno; Indra Gunawan (Yayasan Grace Berkat Anugerah, 2024)
In an era where mobile applications are becoming increasingly important in everyday life, data security and authentication is an aspect that cannot be ignored. Especially in the context of applications that utilize GPS location information, the need to ensure the authenticity and integrity of data becomes crucial. In this study, we introduce an approach to implementing digital signatures to improve data security and authentication in mobile applications based on GPS location. The digital signatures method is used to sign location data generated by GPS devices on mobile applications. This digital signing process allows verification of the authenticity and integrity of that location data. In addition, digital signatures also make it possible to verify the identity of the user or entity that generated the data, thus preventing the possibility of data forgery or other security attacks. This research will include the implementation of a digital signatures-based security system on mobile applications that utilize GPS location services. We will analyze the performance of the system in ensuring the authenticity and integrity of data, as well as measure the overhead incurred by the digital signing process. In addition, we will also test the security of the system by testing for possible attacks or security breaches that may occur. The results of this study are expected to make a significant contribution in strengthening data security and authentication in location-based mobile applications, as well as provide guidance for the practical implementation of digital signatures in this context. Thus, mobile applications that utilize GPS location information can operate with a higher level of security, increasing user confidence in the application.